Современные педагогические технологии в преподавании перевода: рабочая тетрадь - Минин М. Г. Михаил Григорьевич; Ростовцева В. М. Вероника Михайловна; Глухий Я. А. Ярослав Андреевич; Бакало Д. И. Дина Ивановна; Кобенко Ю. В. Юрий Викторович; Николаенко Н. А. Нина Александровна; Шишковская Ю. В. Юлия Владимировна; Сивицкая Л. А. Людмила Анатольевна; Агафонова Л. И. Лидия Ивановна (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана